Finite Element Analysis of Electromagnetic Characteristics of a Single-Phase Permanent Magnet Linear Oscillation Actuator - Hongbin Zhang; Zhaoxin Wang; Minshuo Chen; Zhan Shen; Haitao Yu; Zhike Xu (Sensors)
The electromagnetic characteristics of a single-phase permanent magnet linear oscillation actuator are analyzed by the finite element method. Firstly, the basic structure and operation principle of the linear oscillation actuator are introduced. The internal stator slot and arc tooth are used to reduce the detent force. According to the principle of electromagnetic fields, the electromagnetic field equation is listed and the function of the motor is deduced. At the same time, the eight-node hexahedral element is used to calculate the listed universal functions, and the inductance, flux linkage, induced electromotive force and electromagnetic force of the motor are deduced. The electromagnetic field of the motor is simulated by two-dimensional and three-dimensional finite element methods, and the accuracy of the calculation results of the electromagnetic characteristics of the cylindrical linear oscillation motor by the two methods is compared and analyzed. Finally, an experimental prototype was developed and the no-load characteristics of the motor were tested using the existing linear motor towing method. By comparing the experimental and simulation results, the accuracy of the theoretical analysis and the rationality of the motor design are verified.